Análise do planejamento e gestão de processos e controles construtivos utilizados na construção civil por meio dos Sistemas de Recursos Empresariais – ERP e Modelo de Informação da Construção – BIM: Sienge e Revit. - Sousa, Vitória Helen Almeida (Universidade Federal do Tocantins, 2024)
The civil construction area is one of the oldest activities carried out by man and since the beginning it has been carried out in an artisanal way. Currently, it is seen as one of the most important activities for economic and social development, and it is so important that it participates in about 9% of the country's GDP and generates just over 12,000 new hires, totaling 10% of the total generation. of jobs in Brazil. However, in the midst of so many technological innovations, companies in the field face challenges to remain in the market, directly affecting productivity. In view of the branch's responsibility for the economy, productivity needs to be achieved at its maximum. Thus, the objective was to present the importance and sustainable gains through the use of tools integrated with ERP systems in conjunction with BIM technology.